Analisis Islamic Parenting dalam Penguatan Karakter Prososial Anak: Studi Kasus di RA Tarbiyatun Najah Desa Citapen - Sani Yuniarti; Dinda Hanifah; Hendar Riyadi; Esty Faatinisa; Dina Marlina; Shafi Maulida Fauziah (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to analyze the practice of Islamic parenting in strengthening the prosocial character of early childhood in RA Tarbiyatun Najah, Citapen Village. The background of this research is based on the importance of the role of Islamic parenting in shaping prosocial character as a foundation for children's social-emotional development. Parenting based on Islamic values is believed to be able to instill commendable qualities from an early age, which is an important basis in shaping children's personalities in the future. The research uses a qualitative approach with a case study method, involving direct observation in schools as well as in-depth interviews with teachers and parents. The results of the study show that the implementation of Islamic parenting in the school environment has been carried out effectively, including through the provision of good examples by teachers, the habit of reading daily prayers, strengthening the value of monotheism in teaching and learning activities, and giving appreciation for children's prosocial behavior. Children who are exposed to the practice exhibit behaviors such as sharing, helping friends, working together in groups, and showing empathy for others. However, in the family environment, the practice of Islamic parenting tends to be limited to aspects of worship rituals alone, such as prayer and recital, while moral habituation and direct example have not been carried out optimally. This is due to the lack of understanding of parents about the comprehensive Islamic parenting style and the limited time that parents have to be actively involved in parenting. These findings indicate the need for stronger synergy between schools and families in implementing a balanced Islamic parenting. This study recommends the preparation of special mentoring and training programs for parents to strengthen their role in supporting the formation of children's prosocial character in a sustainable manner through an Islamic approach